Non-pharmaceutical interventions restructured the upper respiratory bacterial microbiota in children under 2 during COVID-19: implications for infection control strategies - Wang, Yufeng; Shen, Wenxin; Xu, Lina; Li, Jiaoyang; Xu, Xuena; Chen, Suqing; Hao, Chuangli; Jiang, Wujun (Frontiers in Microbiology, 2026)
The COVID-19 pandemic substantially altered pediatric respiratory infection patterns. This study assessed the impact of non-pharmaceutical interventions (NPIs) on upper respiratory bacterial epidemiology and microbiota composition in children under 2 years hospitalized with lower respiratory tract infections (LRTIs). Clinical data from 24,159 children admitted between January 2019 and December 2020 were retrospectively analyzed. Following NPI implementation, the overall culture-based bacterial detection rate declined from 61.02% to 18.38%. In an RSV-positive subgroup (pre-COVID-19, n = 95; COVID-19, n = 118), upper respiratory microbiota profiles were characterized using 16S rRNA gene sequencing. Alpha diversity increased significantly, while beta diversity showed distinct community separation between periods (Bray–Curtis distance, PERMANOVA P = 0.01). Taxonomic shifts included increased Proteobacteria and Actinobacteria and reduced Firmicutes, along with decreased Streptococcus and enrichment of Rothia, Dolosigranulum, and Corynebacterium. Overall, NPIs implemented during the COVID-19 pandemic were associated with marked alterations in the upper respiratory bacterial microbiota of RSV-positive young children, highlighting potential implications for future pediatric infection control strategies.